Efeitos de sistemas de manejo pré-semeadura da soja sobre a dinâmica no solo e eficácia de herbicidas - Macedo, Gabrielle de Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The presence of straw on the soil surface can alter the population dynamics of weeds present in the area, and influence the behavior of herbicides in soil. Currently, little is known about the dynamics of release of herbicides with residual effect when your application is performed on the green coverage in the management of pre-sowing soybean, but it is assumed that the distribution and dynamics are altered. This study aimed to evaluate the behavior in soil, the efficiency in weed control and selectivity to the culture of sulfentrazone and flumioxazin herbicide when applied over two types of covers in different desiccation management systems in pre-sowing soybean. There were two experiments, in Botucatu, São Paulo, in areas with millet and sorghum coverage, in a randomized block design with 7 treatments and 4 replications. The treatments were a combination of herbicides in different management systems of coverage crops, which are: glyphosate (720 g e.a. ha-1) 20 days before sowing (DBS) + sulfentrazone (600 g i.a. ha-1) 10 DBS; glyphosate (720 g e.a. ha-1) 20 DBS + flumioxazin (50 g i.a. ha-1) 10 DBS; glyphosate (720 g e.a. ha-1) + sulfentrazone (600 g i.a. ha-1) 10 DBS; glyphosate (720 g e.a. ha-1) + flumioxazin (50 g i.a. ha-1) 10 DBS; sulfentrazone (600 g i.a. ha-1) 10 DBS without the presence of coverage; flumioxazin (50 g i.a. ha-1) 10 DBS without the presence of cover and a control with application of glyphosate (720 g e.a. ha-1) 10 DBS. Were evaluated the availability of herbicides in the soil through periodic collections, weed control, weed survey, selectivity of herbicides to the crop, production and soybean yield components. For quantification of herbicides used a LCMS-MS system consisting of a High Performance Liquid Chromatography (HPLC) coupled with mass spectrometry. For flumioxazin, amounts of herbicide present in the samples were below the detection limit of the analytical method ...

A presença de palha na superfície do solo pode alterar a dinâmica populacional das plantas daninhas presentes na área, além de influenciar o comportamento dos herbicidas no solo. Atualmente, pouco se sabe a respeito da dinâmica de liberação de herbicidas com efeito residual quando sua aplicação é realizada sobre a cobertura verde, no manejo em pré-semeadura da soja, mas supõe-se que sua distribuição e dinâmica sejam alteradas. O presente trabalho teve por objetivos avaliar o comportamento no solo, a eficácia no controle de plantas daninhas e a seletividade para a cultura dos herbicidas sulfentrazone e flumioxazin quando aplicados sobre dois tipos de coberturas em diferentes sistemas de manejo de dessecação em pré-semeadura da soja. Realizaram-se dois experimentos, no município de Botucatu, São Paulo, em áreas com coberturas de milheto e sorgo, com delineamento em blocos casualizados, com 7 tratamentos e 4 repetições. Os tratamentos foram constituídos pela aplicação de herbicidas em diferentes sistemas de manejo das culturas de cobertura, sendo eles: glyphosate (720 g e.a. ha-1) 20 dias antes da semeadura (DAS) + sulfentrazone (600 g i.a. ha-1) 10 DAS; glyphosate (720 g e.a. ha-1) 20 DAS + flumioxazin (50 g i.a. ha-1) 10 DAS; glyphosate (720 g e.a. ha-1) + sulfentrazone (600 g i.a. ha-1) 10 DAS; glyphosate (720 g e.a. ha-1) + flumioxazin (50 g i.a. ha-1) 10 DAS; sulfentrazone (600 g i.a. ha-1) 10 DAS sem a presença de cobertura; flumioxazin (50 g i.a. ha-1) 10 DAS sem a presença de cobertura e uma testemunha com aplicação de glyphosate (720 g e.a. ha-1) 10 DAS. Foram realizadas avaliações da disponibilidade de ...
Effects of management systems pre-planting of soybean on dynamic in soil and effectiveness of herbicides
Keywords: Soja - Semeadura; Erva daninha; Defensivos agrícolas; Plantas - Efeito dos herbicidas; Cromatografia liquida; Lixiviação; Plants, Effect of herbicides on